ACCURACY OF MEASUREMENT RESULTS ON SCHIOTZ TONOMETER TOWARDS GOLDMANN APPLANATION TONOMETER IN TYPE II DIABETES MELLITUS PATIENTS IN MOHAMMAD HOESIN HOSPITAL, PALEMBANG: Oral Presentation - Experimental Study - Ophthalmologist - Fidalia; Erial; AN NASHER, DAMAL (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesThe Goldmann Applanation Tonometer is now the most accurate gold standard compared to othertonometers. IOP measurement errors using the Schiotz Tonometer can be caused by ocular rigidity,where the IOP is read higher in eyes with higher ocular rigidity and vice versa. Type II DiabetesMellitus (DM) patients are at risk for increased ocular rigidity MethodsThis research is a cross-sectional study with a diagnostic test design regarding the accuracy ofintraocular pressure results on the Schiotz Tonometer against the Goldmann Applanation Tonometerin type II Diabetes Mellitus patients with 35 research samples. The research was conducted at theMohammad Hoesin Hospital in Palembang from April 2022 – September 2022 until the sample sizewas met ResultsIntraocular pressure (IOP) as measured by The average Goldmann Applanation Tonometer was 15.5± 2.4 mmHg, with a Schiotz load of 7.5 grams the average was 16.2 ± 2.3 mmHg. Ocular rigidityhad a median of 0.0242 (0.0176 – 0.0341) From the results of this study the IOP examination withthe Schiotz Tonometer had a sensitivity of 92.9%, a specificity of 80.9%, a positive predictive valueof 76.5%, a negative predictive value of 94.4% and an accuracy value of 92.3% indicating astatistically strong level of accuracy ConclusionThe Schiotz tonometer has an accuracy rate of 92.3% in examining intraocular pressure using a loadof 7.5 type II diabetes patients which can replace the Goldmann Applanation Tonometer as the goldstandard if normal ocular rigidity is found